Asistensi Triggers for Decreasing Coffee Purchase Decisions Caused by the Inability of Different Packaging Designs, Narrow Parking Area And Slow In Responding To Complaints - Nur Ikhsan Umam; Nasib Nasib; Debora Tambunan; Ahmad Rivai; Zulia Rifda Daulay (Jurnal Mantik, 2022)
Companies will seek to gain a competitive advantage through improving client purchase decisions. Market changes necessitate a quick response. To meet the company's objectives, all sorts of criticism and suggestions must be properly managed. The goal of this research is to see how packaging design, location, and service quality influence purchasing decisions. This form of study is known as causal research (cause and effect). The research sample consisted of 78 customers from Medan coffee shops. Questionnaires were used to collect data, which was then evaluated utilizing research instrument testing and data analysis procedures such as multiple linear regression analysis. The study's findings show that the location and quality of service have a favorable and significant impact on coffee shop purchases in Medan. While the style of the container has little bearing on enhancing purchasing decisions in Medan coffee shops.